Implementasi Standar Mutu Pendidikan Di SMP Kosgoro Sragi Songgon Banyuwangi Tahun Pembelajaran 2018/2019 - Mahbub, Mahbub; Mawardi, Sumari; Rahmawati, Dewi (Jurnal Manajemen Pendidikan Islam Darussalam, 2019)
This study aims to: Determine the Implementation of the Standards of Quality Education in Junior Kosgoro Sragi Songgon Banyuwangi Learning Year 2018/2019. This study uses qualitative research with the technical analysis interactive model of Miles & Huberman. Key informant principal, Wks. Curriculum, Wks. Student, Wks. Sapras, Treasurer. For Teachers, Students, and Community as supporting data. After getting the data and carry out the analysis, it was found that the implementation of the Standards of Quality Education in Junior Kosgoro Sragi Songgon Banyuwangi Year 2018/2019 Ideal Learning accordance with National Education Standards set by regulation and is developed by BSNP.